Kajian penambahan sorbitol dan teknik pencucian terhadap kualitas fisik kamaboko ikan Belut (Synbrancus bangalensis) - Norhayani Norhayani; Tyas Wara Sulistyaningrum (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
This research aims to gained a new innovative work about diversification of fishery product in a form of eel kamaboko (Synbranchus bengalensis) with best texture, interesting, has optimum durable, high nutrition, had been tested and accepted by the consumer. The data were collected based on the result of the tracking toward physical test. Based on the result of the tests can be conclude that the adding of sorbitol and washing for 3 (three) times affected the improvement of the texture quality and the presentation of eel kamaboko where eel kamaboko that has been produce does not have hollow or cavity and has brighter color. Keywords : Eel (Synbranchus bengalensis), kamaboko, kualitas fisik, sorbitol.